2018
DOI: 10.2307/j.ctv550dd1
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibres in Drug Delivery

Abstract: for their feedback on drafts of the chapters. Professor Mohan Edirisinghe and Professor Kevin Taylor are also thanked for their insightful comments on the manuscript.This book was prepared while CJL was funded by the Engineering and Physical Sciences Council (grant number EP/ P022677/ 1), and we gratefully acknowledge their support of her work. We further thank University College London and King's College London for their support for this endeavour in terms of time, infrastructure and resources.GRW would like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
99
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 30 publications
2
99
0
1
Order By: Relevance
“…Mono-axial electrospinning is the simplest and as a result of this the most common electrospinning experiment. The polymer (and API) in solution or suspension is dispensed through a single-bore blunt-end needle resulting in a monolithic product, with the API and polymer typically evenly and homogeneously blended throughout the fibers [58].…”
Section: Nanofibrous Amorphous Solid Dispersionsmentioning
confidence: 99%
“…Mono-axial electrospinning is the simplest and as a result of this the most common electrospinning experiment. The polymer (and API) in solution or suspension is dispensed through a single-bore blunt-end needle resulting in a monolithic product, with the API and polymer typically evenly and homogeneously blended throughout the fibers [58].…”
Section: Nanofibrous Amorphous Solid Dispersionsmentioning
confidence: 99%
“…20 It has been widely explored to produce materials for a variety of fields, including tissue engineering, biosensors, wound dressings, and drug delivery. [21][22][23] Only a few studies have probed the incorporation of SPIONs into electrospun fibres for biological applications, but there is clear promise: Huang et al reported polystyrene fibres with a high loading capacity of SPIONs, with the resultant formulation effective in killing cancer cells via magnetic hyperthermia. 24 In other work, Wang et al revealed that drug-loaded dehydroxypropyl methyl cellulose phthalate and cellulose acetate fibres encapsulating SPIONs demonstrated superparamagnetism at room temperature, indicating the feasibility of magnetic-field induced release.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning first involves the preparation of a mixed solution of a polymer and drug in a volatile solvent, followed by ejection of this solution through a narrow-bore needle and the application of an electrical field to solidify the product. It is beneficial over other techniques such as spray drying and hot-melt extrusion because it does not require the application of heat, and thus thermally labile active ingredients can be processed [14]. Further, electrospinning allows multiple different fluids to be processed simultaneously, leading to fiber products with highly tunable properties [15,16].…”
Section: Introductionmentioning
confidence: 99%